Structural and optical properties investigation on H-bonded 1D helical self-assembly of 1,1-dibenzyl-3-(2-Bromobenzoyl)thiourea molecules for nonlinear optical application - Lee, Mark Wun Fui; Mohd Faizal Md Nasir,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A benzoylthiourea molecule namely 1,1-dibenzyl-3-(2-bromobenzoyl)thiourea (2BrBT) was synthesized and characterized by C, H, N and S elemental, mass spectrometry and spectroscopic analyses (infrared, ultraviolet-visible and nuclear magnetic resonance). The 2BrBT compound crystallized in a tetragonal system with the space group P43 and exhibits an acentric crystalline packing due to the presence of intermolecular H-bonding network that forms a self-assembly of 1D helical motif. The asymmetric delocalisation of electrons in the molecule retains its transparency throughout the visible and near-infrared region and hence, essentially propagates the macroscopic helical motif in the solid state. The highest-occupied and lowest-unoccupied molecular orbital (HOMO/LUMO) are mainly found on the thiourea moiety and the benzoylthiourea fragment, respectively and shows an optical bandgap of 3.50 eV. The influence of its geometrical characteristics to the optical properties of 2BrBT is established and discussed in view of nonlinear optical (NLO) application.